The attitude of future teachers of musical art to the formation of Event-rt management skills: (according to the results of pilot study) - Chen, Bao; Zelenska, Liudmyla (Professional Art Education, 2024)
Object. The article addresses the importance of developing event-art management skills in the context of training future music teachers. It analyzes the scientific contributions of domestic and foreign scholars dedicated to the issues of art management in the field of music.Methods & methodology. Traditional research methods were used in the article: analysis of scientific and pedagogical literature, empirical and modern art-pedagogical methods.The scientific novelty consists in conducting and highlighting the results of a pilot study regarding the attitude of students of higher education in the specialty 014.13 Secondary Education (Musical Art) to the formation of event-art management skills. The sample consisted of 49 respondents, who were first-level (bachelor's) students of various years at the H.S. Skovoroda Kharkiv National Pedagogical University.Results. The research results indicated that the students are aware of the existence of the art industry and have some understanding of event-art management skills. It was found that the students show interest in creating art products, participating in art projects in various forms, and have a definite interest in the development of current trends in the art market.Conclusions. Considering the intensive development of the art space in Ukraine, there is a need for the active involvement of music teachers in this process, not only at the level of educational institutions, but also at the level of communities. This requires specially organized training of future teachers of musical art as part of the implementation of educational programs, formation of event art management skills in them.Prospects for further research. We believe that with proper substantiation of pedagogical conditions and their implementation in the educational process of institutions of higher education that provide training in the specialty 014.13 Secondary education (Musical art), it is possible to achieve positive results regarding the formation of event-art management skills in future teachers of musical art, which is promising research task.
Keywords: skills; event-art management; art events; future teachers; music; awareness; attitude